Florida Greenhouse Design - R. A. Bucklin (EDIS, 2018)
Greenhouse design considerations are critical in regulating optimal climatic conditions where plants are grown. The structural systems, building components and materials, and machinery equipment play a central role in greenhouse efficiency. Yet, many design considerations vary greatly with region and geography. This article describes greenhouse design considerations specific to Florida’s unique environment. It includes descriptions of framing types and materials, design load consideration with appropriate resources, heating and cooling systems including materials, computer monitoring systems as well as recommendations for maintenance.